Reorganization energy for hole and electron transfer of poly(3-hexylthiophene) derivatives - Oliveira, Eliezer Fernando [UNESP]; Lavarda, Francisco Carlos [UNESP] (Elsevier, 2016)
Poly(3-hexylthiophene) (P3HT) is a common material used as electron donor element in active layers of organic solar cells. Previous studies have shown that is possible to improve the electronic properties of the P3HT through chemical substitutions in the empty beta-position of the thiophene rings; however, up to now it was not reported the effect of chemical substitutions in the charge transport properties of the P3HT. In this work we theoretically investigate the reorganization energy related to the transport of holes and electrons of P3HT and 19 derivatives, employing a combination of density functional theory to calculate the electronic structure and a semiempirical method to optimize the geometry. Our results show that the chemical substitutions are able to improve the charge carrier transfer rate, but certain substituents tend to favour a greater transport of electrons than holes, which is not desirable for polymeric electron donor materials.
Keywords: Density functional theory; Electron transport; Hole transport; P3HT; P3HT derivatives